Synchronous shield tunnelling technology combining advancement and segment fabrication: Principle, verification and application - Yeting Zhu; Yanfei Zhu; Elton J. Chen; Yixin Zhai; Rui Min; Bin Tang; Xin Huang (Underground Space, 2023)
Through the active control of shield thrust system oil pressures, a synchronous shield tunnelling technology combining advancement and segment fabrication was proposed. The key to this technology was to completely exploit the additional stroke of the hydraulic jacks generated by the axial insertion of a key block to assemble the segments. Taking the tunnelling project of the Shanghai Airport Railway Link Line as a demonstration project, this paper uses a large model test platform for this synchronous technology. A single-ring construction process along a straight line was simulated, in which the theoretical external loads were implemented on the shield machine. The feasibility and reliability of this synchronous technology were evaluated considering the accuracy of total thrust force control, maintenance of tunnelling speed and shield postures and segment compression. The effectiveness of the redistribution principle for the missing thrust force due to the withdrawal of cylinders located in the segment fabrication region was discussed. Furthermore, some other interesting phenomena were observed in the practical application in addition to the model test. This technology primarily realizes synchronous assembly by improving the control of the propulsion system of conventional shield machines without any transformation of the shield machine’s primary structure, segment patterns or excavation method. The proposed method has good adaptability and a low construction cost, which will be beneficial for future long-distance tunnelling projects.